Розроблення моделей систем «Інтелектуальний будинок» на базі моделей Маркова - Береговська, Христина; Теслюк, Василь (Видавництво «Редакція «УП», 2016)
This article represents the basic principles of development models, based on Markov models, main purpose of which is to enhance the rapid reaction of the systems class "Smart house".
Keywords: інтелектуальний будинок; модель Маркова; граф станів